Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.4102/phcfm.v13i1.2782
|View full text |Cite
|
Sign up to set email alerts
|

‘It kinda sucks’: Illness perception of a group of South African adolescents with type 1 diabetes mellitus

Abstract: Background: Living with diabetes is challenging, especially for adolescents at risk of poor glycaemic control. Understanding the illness perceptions of this group is important to be able to develop interventions for this growing population in need.Aim: This study explored the illness perception amongst adolescents living with type 1 diabetes (T1D) and how these perceptions interacted with the management of T1D.Setting: This study was conducted at a medical centre providing care for adolescents living with T1D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…27 This new normal was created over time and involved an emotional progression from a range of negative emotions (such as disappointment, sadness and frustration due to feeling different from their peers) to experiencing a sense of normalcy in their daily lives since using CGM, specifically because medical emergencies were less likely with proper management. Negative emotions experienced by adolescents living with T1D are well documented, 28,10,11 but it is important to note that participants in our study also reported feeling empowered by using the monitoring device and experiencing less anxiety as CGM allows individuals to better manage and intervene in their diabetes care plans as it results in the achievement of predictability and control. 16 This feeling of empowerment is similar to the findings of Jonker, 10 who reported that adolescents living with well-controlled diabetes perceive T1D to be manageable and within their control.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…27 This new normal was created over time and involved an emotional progression from a range of negative emotions (such as disappointment, sadness and frustration due to feeling different from their peers) to experiencing a sense of normalcy in their daily lives since using CGM, specifically because medical emergencies were less likely with proper management. Negative emotions experienced by adolescents living with T1D are well documented, 28,10,11 but it is important to note that participants in our study also reported feeling empowered by using the monitoring device and experiencing less anxiety as CGM allows individuals to better manage and intervene in their diabetes care plans as it results in the achievement of predictability and control. 16 This feeling of empowerment is similar to the findings of Jonker, 10 who reported that adolescents living with well-controlled diabetes perceive T1D to be manageable and within their control.…”
Section: Discussionmentioning
confidence: 69%
“…This is in stark contrast with the study of adolescents living with uncontrolled T1D being motivated to adhere to diabetes care plans by fear. 11 The difference in motivating factors for treatment adherence is crucial for the adolescents' well-being -being motivated by fear leads to negative psychological outcomes, whereas our group experienced being empowered by CGM to manage their diabetes better. This finding is similar to those of authors who reported that as adolescents felt more in control of diabetes management, they were encouraged to accept more responsibility for their diabetes management.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, studies in the USA and France found that better diabetes knowledge is associated with glycemic control [16,17], which may suggest the involvement of others factors like socioeconomic status or illness perception for example. It was described in South Africa that adolescents with at-risk glycemic control believed that T1D is di cult to manage, leading to a largely negative perception of the disease [20].…”
Section: Discussionmentioning
confidence: 99%